2017
DOI: 10.1155/2017/9169146
|View full text |Cite
|
Sign up to set email alerts
|

Differential Alterations of the Mitochondrial Morphology and Respiratory Chain Complexes during Postnatal Development of the Mouse Lung

Abstract: Mitochondrial biogenesis and adequate energy production in various organs of mammals are necessary for postnatal adaptation to extrauterine life in an environment with high oxygen content. Even though transgenic mice are frequently used as experimental models, to date, no combined detailed molecular and morphological analysis on the mitochondrial compartment in different lung cell types has been performed during postnatal mouse lung development. In our study, we revealed a significant upregulation of most mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Mitochondria can participate in alveolar epithelial cell activities through complex functions and mechanisms. The number and function of mitochondria continue to increase during postnatal growth and development (El-Merhie et al, 2017). Postnatal mitochondrial changes in AT2, ciliated, and club cells at different stages have been assessed by transmission electron microscopy (TEM) in neonatal mice.…”
Section: Morphological Abnormalities In Mitochondriamentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria can participate in alveolar epithelial cell activities through complex functions and mechanisms. The number and function of mitochondria continue to increase during postnatal growth and development (El-Merhie et al, 2017). Postnatal mitochondrial changes in AT2, ciliated, and club cells at different stages have been assessed by transmission electron microscopy (TEM) in neonatal mice.…”
Section: Morphological Abnormalities In Mitochondriamentioning
confidence: 99%
“…Reduced NAD (NADH) and reduced FAD (FADH2) are the principal substrates for the redox reactions that facilitate electron transfer and OXPHOS through enzyme complexes I and II (Guo et al, 2018). A comparison of the respiratory chain complex I-IV in AT2 and club cells between 15-day-old and adult mice using PCR and western blotting showed that except for succinate dehydrogenase (SDH) complex II, all other complexes increased gradually over time, suggesting that changes in the morphology and number of mitochondria throughout postnatal development are associated with a higher cellular metabolic demand (El-Merhie et al, 2017).…”
Section: Mitochondrial Energy Metabolismmentioning
confidence: 99%
“…To adapt to extrauterine life after birth and for postnatal energy production during lung development, various lung cell types undergo mitochondrial morphological changes, including changes to volume density, size, number and distribution ( 34 ). In the present study, oxygen exposure in new-born rats resulted in a relatively large alveolar cavity, irregularly spaced lungs and a decreased radial alveolar count.…”
Section: Discussionmentioning
confidence: 99%
“…Among recent notable developments, the serotonin transporter/serotonin pathway was reported to be crucial for pulmonary vascular remodeling and adaptation at birth, and in the pathology of alveolar capillary dysplasia with misalignment of pulmonary veins (ACD/MPV) (64), a pathology in which FoxF1 has also been implicated (52). Remaining with studies on clinical material, the role of the mitochondrion in neonatal lung injury is starting to be addressed (123,516), given the report of differential maturation of the mitochondrial compartment according to the individual needs of different cell types during lung development (148). One recent report has indicated that vascular endothelial mitochondrial function may predict death or pulmonary outcomes in preterm infants (254), and hyperoxia in mouse pups has been proposed to deplete pulmonary vein cardiomyocytes, leading to cardiovascular disease in adult mice, through mitochondrial oxidation (643).…”
Section: The Endothelium and The Lung Vasculaturementioning
confidence: 99%